2007
DOI: 10.1158/0008-5472.can-07-0055
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Tumor Metastasis Suppressor Nonmetastatic Protein 23 Homologue H1 and Estrogen Receptor α Alters Estrogen-Responsive Gene Expression

Abstract: Metastasis of cancer cells from the primary tumor is associated with poor prognosis and decreased overall survival. One protein implicated in inhibiting metastasis is the tumor metastasis suppressor nonmetastatic protein 23 homologue 1 (NM23-H1). NM23-H1 is a multifunctional protein, which, in addition to limiting metastasis, has DNase and histidine protein kinase activities. We have identified new functions for NM23-H1 in influencing estrogen receptor A (ERA)-mediated gene expression. Using a battery of molec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 61 publications
1
40
0
Order By: Relevance
“…CATD is constitutively expressed in MDA-MB-231 cells, and levels are not altered by the addition of estrogen. However, the expression of CATD is inhibited when cells are treated with tamoxifen (15,34). EBAG9 has been shown to be expressed at a very low level in MDA-MB-231 cells without the addition of estrogen, and robustly expressed after estrogen treatment in ER␣ positive MCF-7 cells (15).…”
Section: Resultsmentioning
confidence: 99%
“…CATD is constitutively expressed in MDA-MB-231 cells, and levels are not altered by the addition of estrogen. However, the expression of CATD is inhibited when cells are treated with tamoxifen (15,34). EBAG9 has been shown to be expressed at a very low level in MDA-MB-231 cells without the addition of estrogen, and robustly expressed after estrogen treatment in ER␣ positive MCF-7 cells (15).…”
Section: Resultsmentioning
confidence: 99%
“…The same group, also by using NME1 silencing, identified an interaction between NME1 and the macrophage migration inhibitory factor (MIF) that alleviates MIF-mediated suppression of p53 activity (Jung et al 2008). Experiments by Curtis et al (2007) using NME1 siRNA, have shown that NME1, which was reported to interact with the estrogen receptor α, could modulate estrogen responsiveness. Additional studies are needed to further generalize the physiological importance of NME1 and its specificity as compared to NME2, in regulating pathways as important as TGF-β and p53.…”
Section: Nme Silencingmentioning
confidence: 98%
“…Oestrogen is an important mitogen but is also a potent regulator of cell motility and migration resulting from signalling via the oestrogen receptor (Gallo et al 2010), and thus, studies identifying interactions with NMEs immediately raise the question of whether the interactions might augment or modulate ER signalling. As with a number of NME PPIs, studies of oestrogen receptors have identified a high degree of selectivity of interaction with NME proteins: ER-α binds only to NME1 but not to NME2 as shown by co-immunoprecipitation and in vitro studies (Curtis et al 2007), whereas ER-β has only been shown to bind to NME2 (Rayner et al 2008). Curiously, whilst NME1 increases ER-α binding to oestrogen-responsive sequences as determined by gel mobility shift assays, it also promotes a reduction in activity from an oestrogen-responsive reporter construct.…”
Section: Oestrogen Receptorsmentioning
confidence: 99%